A novel catalytic two-step process for the preparation of rigid polyurethane foams: synthesis, mechanism and computational studies. Issue 7 (6th May 2021) - Maiuolo, Loredana; Olivito, Fabrizio; Ponte, Fortuna; Algieri, Vincenzo; Tallarida, Matteo Antonio; Tursi, Antonio; Chidichimo, Giuseppe; Sicilia, Emilia; De Nino, Antonio
Abstract : Synthesis of polyurethane foams catalyzed by sodium chloride both in prepolymer preparation and elongation step. The reaction mechanism involves the role of a proton shuttle between two terminal OH groups of PEG 400. Abstract : Polyurethanes (PUs) are very versatile and popular polymers that play a key role in the automotive, construction and non-food consumable sectors. In general, two-step polyurethane synthetic procedures involve the addition of catalysts also in the second phase of the reaction with problems of high environmental impact and disposal. In this work, an innovative eco-sustainable and very cheap procedure for the production of high-quality rigid polyurethane (PU) foams was developed, starting from polyethylene glycol (PEG 400) and diisocyanates as reagents and using common inorganic salts as catalysts, such as sodium chloride. In particular, our innovatory method is based on a single initial addition of a very cheap catalyst that is proved to be effective for both the prepolymer formation and polyurethane chain elongation. Moreover, simultaneous with the formation of final polyurethane, the salt was restored for a new catalytic cycle. Then, our strategy for polyurethane foam synthesis can surely represent a valid alternative as a very inexpensive and eco-compatible process, also for the industrial field. Finally, detailed mechanistic hypotheses were formulated and supported by DFT calculations.